Faktor Politik dalam Alokasi Dana Antarpemerintah Indonesia - Tobing, M. Syareza L.; Brodjonegoro, Bambang P. S. (UI Scholars Hub, 2013)
The intergovernmental transfer system currently applied in Indonesia is intended to prevent the intervention of political powers. However, there are indications of political determinants behind central government transfers to sub-national governments. In order to prove the existence of these political factors, this research utilizes empirical panel data models of Dana Alokasi Umum (DAU), Dana Dekonsentrasi and Tugas Pembantuan using political variables. Results show that while there are no significant political variables in the DAU and Dana Dekonsentrasi models, there is a political determinant behind the amount of Dana Tugas Pembantuan, where a higher seat share for the Golkar party representing a province in the national parliament will entitle the province to a relatively higher share of the Dana Tugas Pembantuan.